Meta-Analysis the Effect of Chlorhexidine and Povidone Iodine Mouthwashes on Viral Load SARS-CoV-2-Saliva - Danti Narulita; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The strategy to reduce the risk of transmission of COVID-19 is to reduce the salivary SARS-CoV-2 viral load. Chlorhexidine and povidone iodine mouthwash are common active ingredients in oral antiseptics that have efficient viral activity against salivary SARS-CoV-2. This study aims to combine the results of several effect sizes regarding the effect of using chlorhexidine and povidone iodine mouthwash on the salivary SARS-CoV-2 viral load from various countries.Subject and Method: This study is a meta-analysis with the following PICO model, P: COVID-19 patients. I: use of chlorhexidine and povidone iodine mouthwash. C: no mouthwash. O: salivary SARS-CoV-2 viral load. A search for the articles used in this study was carried out using the keywords “COVID-19” OR “SARS-CoV-2” OR “viral load” OR “SARS-Cov-2 viral load” OR “Chlorhexidine mouthrinse” OR “Povidone Iodine mouthrinse ” OR “Randomized Controlled Trial” OR “RCT” between 2012-2022 from the PubMed, Springerlink, Elsevier, Google Scholar and Wiley Online Library databases. The inclusion criteria used in this study were full-text articles using a Randomized Controlled Trial (RCT) design. The analysis used was multivariate with Standardized Mean Difference (SMD). The articles collected were then critically reviewed using the PRISMA checklist, then the data were analyzed using the Review Manager 5.4 tool.Results: This meta-analysis examined 10 articles with a Randomized Controlled Trial (RCT) study design originating from Singapore, Saudi Arabia, Iran, Brazil, Italy, South Korea and Malaysia. A meta-analysis of 7 articles showed that the use of chlorhexidine mouthwash could reduce salivary SARS-CoV-2 viral load by 0.12 units lower than without the use of mouthwash (SMD= -0.12; 95% CI= -0.33 to 0.09; p=0.250). Meanwhile, 7 articles showed that the use of povidone iodine mouthwash could reduce the salivary SARS-CoV-2 viral load by 0.64 units lower than without the use of mouthwash (SMD= -0.64; 95% CI= -1.51 to 0.23; p=0.150).Conclusion: The use of chlorhexidine and povidone iodine mouthwashes can reduce the amount of salivary SARS-CoV-2 viral Keywords: mouthwash, chlorhexidine, povidone iodine, COVID-19, salivary SARS-CoV-2 viral load.Correspondence: Danti Narulita. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: dantinarulita@yahoo.co.id. Mobile: +6282158818400.Indonesian Journal of Medicine (2022), 07(04): 387-400https://doi.org/10.26911/theijmed.2022.07.04.04